(3eNJUQ aj GdJGQjNs
(3ChdgG (B:s
(3GdMeO ddg eUhQ GdOghQ , heMUi GdCYhGe hGdTghQ CeG HYO agPG eNJUQ ef cJGH GdJGQjN aChd Pdc JGQjN GdEScfOQ s
(3BNQgG (B:s
(3jfJgi HMhGOK SfI SJ hJeGfeGFI hBNQ eG ajg (B: (3hJQLeI JeQ (B[ (3JeQdfc (B] (3PcQJgG ai eMdgG hai gPG GdbOQ caGjI ef PcQ gPg GdSfI hGdMeO ddg hMOg s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3eQJH Ydi GdSfhGJ s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs